URGENSI MEMAHAMI PANCASILA DI ERA KONTEMPORER - ARIA KAREBET; FREYA AZALIA ARDIYANTI; MOHAMMAD ALDIO HENDICO; RISKA ANDI FITRIONO (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
Pancasila is the ideology and basis of the Indonesian state, where the existing precepts can be a guide for society in behavior and statehood. Therefore, an understanding of Pancasila and also threats to the ideology of Pancasila is an important urgency to be spread in order to maintain the ideology of Pancasila and in general, the Indonesian people and state. Pancasila values contained in the five precepts of Pancasila are divine values, human values, unity values, people's values and social justice values. The practice of Pancasila in daily life is very important for everyone to maintain community life in Indonesia. However, over time, the ideology of Pancasila began to fade due to the many threats that tried to undermine the ideology of Pancasila, even though Pancasila itself is a form of the personality of the Indonesian nation. Therefore, we as Indonesians should understand and maintain the essential values of the Pancasila ideology. By understanding the essence of Pancasila, as well as understanding the threats that can threaten the existence of Pancasila, we can be one step ahead in being good citizens.